The effect of perceived value on service satisfaction in brand image mediation (Case study toward accounting student, Faculty of Economics, State University in East Java) - Choiriyah, Siti Nur; Ekowati, Vivin Maharani; Oktaviana, Ulfi Kartika (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2017)
This study aims to examine, test, and examine the effect of Perceived Value on Service Satisfaction. Testing the role of Brand Image as a variable mediation influence Perceived Value on Service Satisfaction. The research was conducted in Accounting Department of Faculty of Economics, Surabaya State University, Airlangga University Surabaya, State Islamic University Maulana Malik Ibrahim Malang, Brawijaya University, and State University of Malang. The population of this study are all students of Accounting Department of Economics Faculty of State University in East Java as many as 5,366 students. The sample of this research is 98 students. Data collected directly from resonden by using research instrument in the form of questionnaire and technical data using Path Analysis. The results show that Perceived Value has a significant effect on brand image. Brand image mediates the influence of Perceived Value on Service Satisfaction, where the image of the brand image as a full mediation. Based on these results, it can be interpreted that every member of the organization should be able to create and maintain excellent service provided to students, so that students feel safe and comfortable to perform activities that are closely related to organizational goals, and not reluctant to perform activities that can increase the value that customers perceive to the organization. With a good understanding of the basic concepts of service satisfaction that are firmly rooted in the mind of a student, the student will show the satisfaction of the various forms of service as well. Students will tend to think that the satisfaction of the service is received in accordance with the perceived value of the sacrifice of the cost given to it in obtaining the service. The better the services provided by the department to the students the better the assessment given by the student. So that good service brings out the brand image itself against a student in the State College.Keyword: Perceived Value, Service Satisfaction, Brand Image